Blending in Advertisements for Events - Salsabila Bunga Sangsthita; Rio Rini Diah Moehkardi (Lexicon, 2018)
Blending is often used in copywriting since the construction of the new words in blending is eye-catching. This paper investigates how blends are constructed in advertisements for events. The data for the research were obtained from advertisements for events held in Yogyakarta from 2014 to 2017. The data were analyzed using Hosseinzadeh’s (2014) classification to determine the type of blends by reconstructing them and which type the most frequently used. The results show that 50 blends were found in the advertisements. Blends belonging to Types 1, 2, 3, 5 were used almost equally frequently, i.e., 22%, 20%, 20%, 28% respectively. Only two Type 4 blends (4%) were found and Types 6 and 7 blends were not found at all. However, three new blends were found (6%).